Using the Scrum Method to Developing Population Information System - Wahyu Setyaningsih, Putry; Witanti, Arita; Widatama, Krisna (Universitas Multimedia Nusantara, 2024)
The adoption of Population Information System is crucial to enhance work effectiveness and serves as a manifestation of transparency in population data management. The complexity from design to implementation of such a population information system poses its own challenges. There are at least three main issues in system design, namely time estimation, team management, and ensuring the quality of system being developed. These issues must be addressed early on to prevent potential team management problems during the design and development stages of the application. One suitable method that can be employed for the design of the population information system is the Scrum methodology. Scrum is a software development framework that emphasizes a collaborative and adaptive approach. It falls under the Agile methodology, aiming to produce products that are more responsive to changes and enabling teams to adapt quickly in a dynamic environment. Scrum also promotes transparency in the development process, aiding in monitoring system progress and information accuracy. Compared to the commonly used Waterfall method, the Scrum approach offers greater flexibility in dealing with changes in requirements or needs that may arise during the development process. While the Waterfall method tends to follow predefined in linear steps. The novelty of this research lies in the proactive approach to addressing the complexity of designing population information systems by implementing Agile methodologies such as Scrum. Thus, it is expected that the implementation of Scrum will bring significant changes in improving the effectiveness and transparency in the development of population information systems.